Korean red ginseng formula attenuates non-alcoholic fatty liver disease in oleic acid-induced HepG2 cells and high-fat diet-induced rats - Min Zheng; Yang Li; Zhiying Dong; Yibo Zhang; Zhichao Xi; Man Yuan; Hongxi Xu (Heliyon, 2023)
Objective: Non-alcoholic fatty liver disease (NAFLD) is the leading chronic liver disease. We have developed a Korean Red Ginseng Formula (KRGF) containing extracts of Korean Red Ginseng (KRG), Crataegus Fructus, and Cassiae Semen. In this study, our aims were to investigate the therapeutic potential and underpinning mechanisms of KRGF in NAFLD complicated by hyperlipidemia. Methods: In the in vitro assays, HepG2 cells were treated with KRGF for 24 h in the presence or absence of oleic acid (OA). To assess the in vivo protective effect of KRGF against NAFLD, rats fed a high-fat diet (HFD) were given intragastric administration for 30 days. Results: KRGF exerted protective effects against NAFLD by reducing lipid accumulation and steatosis in OA-stimulated HepG2 cells and HFD-fed rats. In HFD-fed rats, KRGF effectively decreased triglyceride levels in both blood and liver tissue and modulated the expression of key regulators of lipogenesis and fatty acid oxidation. KRGF downregulated the expression of lipogenesis factors, namely C/EBPα, FAS, SREBP-1c, and PPARγ, while upregulating the expression of PPARα and CPT-1, thus promoting fatty acid oxidation. Additionally, KRGF intensified the phosphorylation of AMPK and ACC, which are two enzymes that suppress fatty acid synthesis and promote fatty acid oxidation. KRGF effectively decreased total cholesterol (TC) levels in both blood and liver tissue, and it modulated the expression of major enzymes related to TC metabolism, namely apoB, ACAT2, CYP7A1, and HMGCR. Conclusion: In conclusion, KRGF mitigated NAFLD complicated by hyperlipidemia by modulating triglyceride and cholesterol metabolism, suggesting its potential for future development in the treatment of NAFLD.